148k views
2 votes
Combine the terms and write the answer as one logorithm. Please show work.

Combine the terms and write the answer as one logorithm. Please show work.-example-1

1 Answer

4 votes

Answer:
ln(x^{(1)/(4)}y^{(1)/(2)}z^{(2)/(3)})

Explanation:

Formula:


k* ln(a)=ln(a^(k))


ln(a)+ln(b)=ln(ab)


ln(a)-ln(b)=ln((a)/(b))


(1)/(4)* ln(x)=ln(x^{(1)/(4)})


(-1)/(2)* ln(x)=ln(x^{(-1)/(2)})


(2)/(3)* ln(x)=ln(x^{(2)/(3)})

Working:

So,
(1)/(4)ln(x)-(1)/(2)ln(y)+(2)/(3)ln(z)=ln(x^(1)/(4))-ln(y^(-1)/(2))+ln(z^(2)/(3))

=
ln(\frac{x^(1)/(4)}{y^{(-1)/(2)} } )+ln(z^{(2)/(3)})

=
ln(x^(1)/(4)}{y^{(1)/(2)}z^{(2)/(3) })

User Amit Dube
by
6.3k points